Ecology and behavioral response of Ruddy Shelduck (Tadorna ferruginea) in the wetland complex of Oued Righ valley (Algerian Sahara). - NOUIDJEM, Yassine (Algerian Journal of Biosciences, 2021)
The wetland complex of Oued Righ valley accommodates a population of Ruddy Shelduck (Tadorna ferruginea) between 2012 and 2014, the total reached 80 individuals in the Lake Hamraia where the species wintering. The analysis of the diurnal time budget of wintering populations revealed the role of feeding area delivery for this species and they devoted their day time to feeding (51.2%), sleeping (18.8%), followed by swimming activity (6.3 %), and courtship activities with flying (2.03%) which often occurs after disturbances caused by human or by Marsh harrier (Circus aeruginosus). It is interesting to study the behavior of these ducks in Saharan bioclimatic area and follow the phenology and characteristics in order to preserve the biodiversity in this region.